“Through the Patience of the Scriptures” : Romans 15:4, Divine Patience, and the Fittingness of Holy Scripture as Text - Alexander, Thomas (Lumen et Vita, 2024)
Is Holy Scripture a text? Curiously enough, modern theologians in the West are of a divided mind. Some have argued that Scripture is not defined by what it is (i.e., a text), but rather, by what it is for (i.e., for the use of the Church) or where it is from (i.e., primitive oral traditions), both inherently non-textual accounts of Scripture. Such critiques tend to conclude that, ultimately, it is unfitting for Holy Scripture to be a text. This essay resists such tendencies by taking up a generative, though often overlooked, passage in the apostle Paul’s epistle to the Romans. I argue that Romans 15:4 teaches that Holy Scripture is a patient text, and the patience of Holy Scripture’s textuality fittingly conveys the patience of God Himself. This essay builds upon theological writings from within Reformed Protestantism, including John Calvin, Karl Barth, and John Webster, as well as Paul Dafydd Jones’ recently unveiled and still unfolding theological exploration of divine patience.